Surface Modification of Sisal Fiber Reinforced Polymer Composites: Literature Review - Pipathattakul, Manop; Surin, Prayoon; Wongon, Jessada (Journal of Advanced Development in Engineering and Science, 2023)
This article aims to review about the different surface treatments applied to natural fibers and focused on sisal fiber for advanced composites applications. Natural fibers are a promising reinforcement for use in composites on account of its low cost, low density, high specific strength and modulus, no health risk, easy availability in some countries, renewability, and ready biodegradability. However, the main disadvantages of natural fibers in composites are the low compatibility between fiber and matrix and high degree of moisture absorption. Therefore, physical and chemical treatments are conducted for modification of the fiber surface properties. The different physical/chemical modifications on natural fibers for use in natural fiber reinforced polymer composites have been reviewed. Physical/chemical treatments including corona, plasma, alkaline, silane, acetylation, benzoylation, peroxide, maleated coupling agents, sodium chlorite, acrylation, isocyanate, stearic acid, permanganate, triazine, fatty acid derivate and fungal are discussed. The various methods for treatment of fiber aimed to improve the adhesion between the fiber surface and the matrix may not only adjust the fiber surface but also increase fiber strength properties. Moreover, moisture resistance and mechanical properties of composites are improved.